Channel Finance - Financing of Accounts Receivable by Banks in Homogeneous Distribution Channels - Poskart, Robert (Channel finance - finansowanie należności przez banki w jednorodnych kanałach dystrybucyjnych, 2010)
The article focuses on an innovative tool in Poland i.e. the programme of financing customers channel finance. The article discusses the advantages of the tool such as increasing the level of liquidity of the enterprises and the optimisation of costs and consumer loyalty. Is should be reckoned that in the future more and more enterprises will realize various types of the programme in agreement with banks.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 132-143
Keywords: channel finance; financing consumers; liquidity; bankruptcy